Assessment of renovation measures for a dwelling area – Impacts on energy efficiency and building certification. (15th February 2016) - Ramírez-Villegas, Ricardo; Eriksson, Ola; Olofsson, Thomas
Abstract: The European Union has an ambitious plan to reduce energy use and emissions by the year 2030. The building and real estate sectors have a great potential to help reduce emissions by energy efficiency. However, different energy sources and environmental standards affect the decision making of these major renovations in the existing stock. This study investigates how different renovation strategies affect the energy rating of a selected Building Environmental Assessment Tool and analyses the consequences in terms of greenhouse gas emissions for the local district heating system. Both building energy simulations and energy systems cost optimization were used to determine the energy use and local emissions. The results of different renovation scenarios were used to evaluate the rating in the selected tool and the impact in the district heating local emissions. The used methodology illustrates how energy efficient renovation impacts on the district heating system's local emissions. However, a bias towards resource classification within the Swedish Building Environmental Tool, Miljöbyggnad, needs to be addressed in order to assess the impact of local emissions. Highlights: How renovation affects energy rating in a Building Environmental Assessment Tool. Analyse the consequences in terms of GHG emissions from the district heating system. Similar improvements from different renovation strategies. Biases in the Building Environmental Assessment Tool in emissions classification. A clear picture of renovation impact on the local energy system.